(untitled) (E Global Congress, 2024)
In the further development of the pharmaceutical industry and the improvement of the quality of medicines, it is crucial to train the personnel of the field and improve their qualifications, and develop pharmaceutical science. An important role was played by the establishment of the pharmaceutical department in medical institution.